Characterization, Classification, and Evaluation of the Reservoir Pore Structure Features of Lacustrine Fine-Grained Sedimentary Rocks. A Case Study of the Fourth Member of the Shahejie Formation in the Chenguanzhuang Area of the Southern Gently Sloping Zone of the Dongying Depression, Bohai Bay Basin - Yang, Yiming; Peng, Jun; Xu, Tianyu; Wang, Yubin; Zeng, Yao (Frontiers in Earth Science, 2022)
With the development of unconventional oil and gas exploration “from sea to land,” lacustrine fine-grained sedimentary rocks (FSR) have gradually attracted the attention of scholars and become an important topic in the field of unconventional oil and gas, but the research is still in its initial stage. In this study, lacustrine FSR in the Dongying Depression of the Bohai Bay Basin are used as the research object, and nuclear magnetic resonance (NMR) and quantitative image characterization are used to characterize the pore structure of the reservoir in the study area on multiple scales, analyze the reservoir characteristics control factors, and classify and evaluate the reservoir. The results show that: 1) the favorable petrographic phases of the FSR reservoir can be classified into six types of organic-rich lime mudstone, organic-rich laminoid lime clay rock, organic-rich laminoid clay micritic limestone, organic-bearing banding clay micritic limestone, organic-rich banding lime clay rock, and organic-bearing lumpy clay micritic limestone. With an average porosity of 12.3% and an average permeability of 10.58 mD, the overall reservoir is a typical low-porosity-low-permeability type; 2) the reservoir space types are diverse, with strong microscopic inhomogeneity; pores with a pore size of less than 2 nm almost have no contribution to the reservoir space; the pore volume and pore area are mainly provided by organic matter pores at the 100 nm level, mineral intergranular pores, and clay mineral shrinkage pores/slits. The FSR reservoirs in the study area are classified into three categories, and the pore structure of the reservoirs from categories I to III deteriorates in turn. This study provides a basis for the microscopic characterization, classification, and evaluation of lacustrine FSR reservoirs and their exploration.